72.5k views
4 votes
Plsss help ASAP :) :)

Plsss help ASAP :) :)-example-1
User Piris
by
5.7k points

1 Answer

8 votes

Answer:

steps below

Explanation:

Step 1: Cot A / (1+cot A) * Cot B / (1+cot B )

= (Cot A * Cot B) / ((1+cot A) *(1+cot B ))

= (Cot A * Cot B) / (1+cot A+cot B+cot A cot B)

= (Cot A * Cot B) / ((1+cot A+cot B)+ (cot A cot B)) : a

Step 2: (cot A * cot B -1) / (cot A + cot B) = cot (A+B) = cot 225° = 1 (formula)

cot A * cot B -1 = cot A + cot B

cot A * cot B = 1 + cot A + cot B (substitute a)

Step 3:

Cot A / (1+cot A) * Cot B / (1+cot B )

= (Cot A * Cot B) / ((cot A * cot B)+ (cot A * cot B))

= (Cot A * Cot B) / (2 * (cot A * cot B))

= 1 / 2

= 0.5

User Ivan Kashtanov
by
5.2k points